Theresian reform efforts in the regulation of the socioeconomic position of Roma in Croatia and Slavonia (Povijesni prilozi (Historical Contributions), 2019)
The history of the Roma population on the Croatian area was marked by the periodsin which the Roma faced the impact of the repressive and assimilatory policy of thestate and local authorities towards them. Th e period of the reign of Maria Theresa andJoseph II was marked by such a policy, as they issued numerous decrees on Roma. Themain goal of this policy was to reform the status of the Roma population by orderingthem the forced sedentarization, the prohibition of their identity, e.g. their name, theuse of their language and customs, doing their traditional professions and so on. Asthe result of such a policy, the Roma should have become the integrated part of theHabsburg society. The similar enlightened policy toward the Roma was conducted bythe other European rulers as well. Th is paper is based on the research of the archivalfonds of the Croatian State Archives, as well as the analysis of the relevant literature.